1991
DOI: 10.1002/bip.360311008
|View full text |Cite
|
Sign up to set email alerts
|

Valinomycin and its interaction with ions in organic solvents, detergents, and lipids studied by Fourier transform IR spectroscopy

Abstract: The structure of valinomycin in a range of organic solvents of varying polarity and in detergent and lipid dispersions has been studied by Fourier transform ir spectroscopy. In solvents of low polarity such as chloroform, ir spectra of valinomycin are fully consistent with the bracelet structure proposed on the basis of nmr spectroscopy, showing a single narrow amide I component attributable to the presence of beta-turns and a single band arising from nonhydrogen-bonded ester C = O groups. K+ complexation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 12 publications
1
34
0
1
Order By: Relevance
“…The FTIR spectra of peptides XXIII and [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] before (XXIII H , [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] H ) and after deuteration (XXIII D , [1][2][3][4][5][6][7][8][9][10][11][12][13]…”
Section: Ftir Spectra In Dmso and Dmso/d 2 Ounclassified
See 2 more Smart Citations
“…The FTIR spectra of peptides XXIII and [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] before (XXIII H , [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] H ) and after deuteration (XXIII D , [1][2][3][4][5][6][7][8][9][10][11][12][13]…”
Section: Ftir Spectra In Dmso and Dmso/d 2 Ounclassified
“…The related Fourier self-deconvolution (FSD), second derivative (2ndD), and 4thD curves (A H -C H and A D -C D ) are reported in Figure 2 (XXIII) and ). It should be noted that, only the figures concerning peptides XXIII and [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] are presented here, although similar measurements were performed on all peptides listed in Table I. The application of BN methods to all peptides, after subtraction of the H 2 O or D 2 O baseline spectra, is summarized in Table II. Peptide XXIII presented amide I components at wave numbers close to those found for XXIV, including the minor components below 1650 cm Ϫ1 .…”
Section: Ftir Spectra In Dmso and Dmso/d 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…It is an antibiotic produced by Streptomyces fulvissimus and is a dodecadepsipeptide composed of three identical fragments that form a 36-member macrocycle (Figure 1). Valinomycin binds to alkali (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), alkaline earth (7,12,16), transition metal (12,17) and ammonium ions (8) in solution. It is highly selective for potassium ions over sodium ions in solution, and its function as an antibiotic is based on selective transport of potassium over sodium ions across biological membranes (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…It is highly selective for potassium ions over sodium ions in solution, and its function as an antibiotic is based on selective transport of potassium over sodium ions across biological membranes (1,2). The interaction between valinomycin and metal ions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), in particular alkali metal ions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), has been studied extensively by a variety of experimental techniques, including NMR (3-6, 11, 15, 16), infrared (IR) (6,8,11,17), circular dichroism (CD) (15,17) and Raman (7,13) spectroscopy as well as mass spectrometry (9,10,12). In recent years, computational studies (18) pertaining to the binding of valinomycin to cations have also been reported.…”
Section: Introductionmentioning
confidence: 99%